Identifying choremes in mental maps to better understand socio-spatial representations - Sylvain Dernat; François Johany; Sylvie Lardon (Cybergeo)
There is a large body of scientific literature examining mental maps from a variety of disciplinary approaches. In this article we propose a specific method combining geography and social psychology to elicit and analyze socio-spatial representations in mental maps. To illustrate this method, we chose a case study of rural career choices envisioned by veterinary students. We combined textual analysis of student discourses with choremes analysis of both graphical representations and discourse to reveal how students represent socio-spatial aspects of a rural veterinary profession in mental maps. The results show that students’ representations reflect various combinations of spatial organization principles. This method provides a means of better understanding socio-spatial representations.